Thermodynamics of DNA: sensitizer recognition. Characterizing binding motifs with all-atom simulations. Issue 48 (28th November 2016) - Gattuso, Hugo; Dumont, Elise; Chipot, Christophe; Monari, Antonio; Dehez, François
Abstract : We report the investigation of the thermochemical properties of benzophenone interacting with B-DNA studied by all-atom molecular dynamic simulations. Abstract : We report the investigation of the thermochemical properties of benzophenone interacting with B-DNA studied by all-atom molecular dynamic simulations. In particular, we determine the binding free energy for two competitive binding modes, minor groove binding and double insertion. Our results allow us to quantitatively resolve for the first time the mode of binding of this paradigmatic photosensitizer, indicating a marked preference for minor groove binding. Furthermore, we have settled a protocol allowing for the determination of binding energies in the case of non-covalent interaction with DNA, in particular, tackling the non-trivial problem of the strong reorganization of the DNA imposing extended statistical sampling. Our contribution paves the way to the systematic determination of the thermochemical properties of drugs or pollutants interacting with DNA.